The influence of more concentrated energy distribution formed by an aspheric lens with eliminated spherical aberration on laser-induced air breakdown. Issue 12 (16th November 2022) - Li, Shenglin; Hu, Zhenlin; Zhou, Yunpeng; Zhang, Deng; Wang, Weiliang; Gu, Yang; Sattar, Harse; Cheng, Wen; Guo, Lianbo
Abstract : Using an aspheric lens for laser focusing solves the energy dispersion caused by spherical aberration, reducing the plasma fluctuations. Abstract : In this work, we study the influence of energy distribution caused by spherical aberration on laser-induced air breakdown. We achieve more concentrated energy distribution using an aspheric lens with eliminated spherical aberration. The effects of the laser energy dispersion caused by spherical aberration on the plasma evolution are analyzed from laser energy absorption, temporal evolution images, and spectra of plasma. The energy distribution of laser focusing with different lenses is simulated and analyzed. The concentrated energy distribution achieved by the aspheric lens increases the laser energy absorption rate and reduces the fluctuations of the laser-induced air plasma and spectrum. In detail, we demonstrate the plasma temporal evolution process formed by the aspheric lens and explain the fluctuations' decrease. The result provides the basis for an in-depth understanding of the evolution process of laser-induced air plasma. The increase in laser absorptivity is beneficial for laser focusing applications that require the breakdown of low absorptivity samples such as gaseous and aerosol states samples.